A Comparative Study of the Approach of Imam ‘Ali (AS) and Āl-e Bouyeh Government (Baghdad Branch) to the Christians - Abbas Rahbari; Ayub Tahmazi (پژوهش در آموزش معارف و تربیت اسلامی)
The purpose of the present research is to study the approach of Imam ‘Ali (AS) and Āl-e Bouyeh government (Baghdad Branch) to the Christians. The method of study is descriptive-analytical and the results showed that although the duration of Imam ‘Ali’s government was so short, it had abundant achievements and outcomings and it was derived from the Qur’an and Sirah of the Holy Prophet of Islam (PBUH). Following the governmental style of Imam ‘Ali (AS), Āl-e Bouyeh attempted to observe cautious aspects in their encounter with the Christians and treated them according to the Islamic instructions such as equality and brotherhood. Although their measures were not as complete as the ones in Imam ‘Ali (AS)’s government, yet it can be concluded that the measures of Imam ‘Ali (AS) have been referenced as a suitable role model for the Muslims in that period. During the governments of ‘Alavi and Āl-e Bouyeh, common people and the Christians were treated appropriately and they had relative welfare. The Christians’ condition in the Shi’ite Bouyeh society was by far better than their condition in other places. Bouyeh governors were observing the utmost accuracy and attempt so that religious minorities especially the Christians in their territory had welfare. Adoption of this policy caused the presence, cooperation, and employment of some Christians in the Bouyeh government and it led to Islamic Renaissance. The approach of many Bouyeh officials and governors to the Christians was similar to the method of the ‘Allavis.